Effects of Listener Age and Native Language Experience on Recognition of Accented and Unaccented English Words - Gordon-Salant, Sandra (J Speech Lang Hear Res, 2019)
PURPOSE: Older native speakers of English have difficulty in understanding Spanish-accented English compared to younger native English speakers. However, it is unclear if this age effect would be observed among native speakers of Spanish. The current study investigates the effects of age and native language experience with Spanish on the ability to recognize words spoken in English by Spanish-accented and unaccented talkers. METHOD: English monosyllabic words, recorded by native speakers of English and Spanish, were presented to 4 groups of listeners with normal hearing: younger native Spanish listeners (n = 15), older native Spanish listeners (n = 16), younger native English listeners (n = 15), and older native English listeners (n = 15). Speech recognition accuracy was assessed for the unaccented and accented words in both quiet and noise. RESULTS: In all conditions, the native English listeners performed better than the native Spanish listeners. More specifically, the native speakers of Spanish consistently recognized accented English less accurately than the native speakers of English, demonstrating no advantage of shared native language experience between nonnative listeners and accented talkers. Older listeners in the native Spanish language group also performed less accurately than their younger counterparts, for English words spoken by both unaccented and accented talkers. Finally, whereas listeners who were native speakers of English showed marked declines in recognition of Spanish-accented English relative to unaccented English, listeners who were native speakers of Spanish (both younger and older) showed less decline. CONCLUSIONS: The general pattern of results suggests that both native language experience in a language other than English and age limit the ability to recognize Spanish-accented English. The implication of the overall findings is that older nonnative listeners will have considerable difficulty in understanding English, regardless of the talker's accent, in both clinical and everyday listening situations.